EXPECTATIONS ON THE XXI CONFERENCE OF THE PARTIES - Macines Romero, Rogelio Nicolás (2015)
One of the major global problems that is affecting society and particularly the lower social strata is related to the environment and climate change. The earth poles are losing ice as well as glaciers in our country are melting, weather events are becoming more intense: hurricanes, storms, typhoons, droughts, El Niño.Although there is greater consensus on the potential serious damage, countries for various reasons have not yet found a way to continue the path indicated by the Kyoto Protocol, taking a new opportunity in the XXI Conference of the Parties in December 2015 in Paris.In this article we analyze two of the reasons that make difficult for countries to agree: 1. The level of economic activity of the countries is expressed on their rates of growth. If this growth is low, the issue of climate change is relegated; 2. The oil is considered to be the main source of energy used worldwide and it is also the major source of environmental pollution.